Triazine Derivative as Putative Candidate for the Reduction of Hormone-Positive Breast Tumor: In Silico, Pharmacological, and Toxicological Approach - Tayyab Imtiaz, Muhammad; Anwar, Fareeha; Saleem, Uzma; Ahmad, Bashir; Hira, Sundas; Mehmood, Yumna; Bashir, Manal; Najam, Saima; Ismail, Tariq (Frontiers in Pharmacology, 2021)
Background and objectives: Breast cancer is a heterogeneous disease that poses the highest incidence of morbidity among women and presents many treatment challenges. In search of novel breast cancer therapies several triazine derivatives have been developed for their potential chemotherapeutic activity. This study aims to evaluate the NMU-induced anti-mammary gland tumor activity of 2,4,6 (O-nitrophenyl amino) 1,3,5-triazine (O-NPAT). Methods: The in-silico modeling and in-vitro cytotoxicity assay were performed to strengthen the research hypothesis. For in-vivo experimentation, 30 female rats were divided into five groups. Group, I (normal control) received normal saline. Group II (disease control) received NMU 50mg/kg. Group III (standard control) was treated with tamoxifen 5mg/kg. Group IV-V received O-NPAT at the dose of 30mg/kg and 60mg/kg respectively. For tumor induction 3 intra-peritoneal doses of NMU were given at 3 weeks interval whereas all treatment compounds were administered orally for 14 days. Biochemical and oxidative stress markers were estimated. Inflammatory markers were also measured for the analysis of inflammation. Hormonal profile of progesterone and estrogen were also estimated. Results: The test compound presented a significant reduction in organ weight and restored the hepatic and renal enzymes. O-NPAT treatments enhanced the anti-oxidant enzyme levels of Catalase (CAT), superoxide dismutase (SOD), and sulfhydrl (TSH) with a highly significant reduction in lactate dehydrogenase (LDH) and lipid peroxidation. Also, the decrease in fragmented DNA, hormonal levels (E2, PR), and inflammatory cytokines (IL-6, TNF-α) justified the dosage efficacy further supported by histopathological findings. Conclusion: All results indicated the chemopreventive potential of O-NPAT and its further possibility of exploitation for beneficial effects in breast cancer treatment.